The impact of blockchain on Smes’ sustainability. The case of an apulian wine company - Dicuonzo, Grazia; Donofrio, Francesca; Ranaldo, Simona; Turco, Mario (Piccola Impresa / Small Business, 2021)
The Italian business system, characterized mostly by the presence of SMEs, makes interesting the analysis of the tools that promote their growth, including through investments in new digital technologies. Among these, the blockchain has the potential to ensure greater transparency of business processes, supporting their competitiveness and sustainability. SMEs show an attitude of closure towards the digitization process, very often neglecting the benefits both in terms of economic-financial performance and improving competitiveness and corporate sustainability. In light of the limited theoretical contributions on the subject, this study aims to analyze the relationship between sustainability and digital technologies in SMEs, analyzing a case study operating in the wine sector. The results show an increasing attention of SMEs to digital innovation, recognizing their potential advantages in terms of improving corporate sustainability policies.